Interventions for adults with deafblindness - an integrative review - Camilla Warnicke; Moa Wahlqvist; Agneta Anderzén-Carlsson; Ann-Sofie Sundqvist (BMC, 2022)
Abstract Purpose To compile the current research on interventions for rehabilitation aimed at adults (aged 18-65 years) with deafblindness. Materials and methods A comprehensive search was conducted in eight databases. An additional manual search was also carried out. A total of 7049 unique references were initially identified, and after screening, 28 original scientific articles were included. The results from these articles were categorized based on limiting consequences of deafblindness: communication, orientation and to move around freely and safely and access to information, as well as to psychological adaptation to deafblindness. Results Fourteen of the included articles had their main focus on access to communication, ten on orientation and the ability to move around feely and safely, three on the opportunity to gain access to information, and one related to psychological adaptation to deafblindness. Most articles focused on technical devices, of which one-third were single case studies. Conclusion There is a limited number of evaluated interventions for people with deafblindness. Most of the existing studies involved one to five participants with deafblindness, and only few studies involved a larger number of participants. More research with a larger number of participants are needed, which could be facilitated by international cooperation between practitioners and researchers.